2011
DOI: 10.1099/ijs.0.022368-0
|View full text |Cite
|
Sign up to set email alerts
|

Alcanivorax pacificus sp. nov., isolated from a deep-sea pyrene-degrading consortium

Abstract: A taxonomic study was carried out on a novel bacterial strain, designated W11-5 T , which was isolated from a pyrene-degrading consortium enriched from deep-sea sediment of the Pacific Ocean. The isolate was Gram-reaction-negative and oxidase-and catalase-positive. Growth was observed in 0.5-12 % (w/v) NaCl and at 10-42 6C. On the basis of 16S rRNA gene sequence analysis, strain W11-5 T was shown to belong to the genus Alcanivorax with a close relation to A. dieselolei B-5 T (93.9 % 16S rRNA sequence similarit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
31
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 19 publications
0
31
0
Order By: Relevance
“…In this study, we describe a novel strain, pht-3B T , which was isolated from a pyrene-degrading consortium from an enriched deep-sea sediment sample collected from the western Pacific Ocean (Wang et al, 2008) and shown to be phylogenetically related to members of the genus Nitratireductor. At the time of writing, four novel species from this pyrenedegrading consortium have been described: Roseovarius pacificus , Oceanicola pacificus (Yuan et al, 2009), Bowmanella pacifica (Lai et al, 2009) and Alcanivorax pacificus (Lai et al, 2011a).…”
mentioning
confidence: 99%
“…In this study, we describe a novel strain, pht-3B T , which was isolated from a pyrene-degrading consortium from an enriched deep-sea sediment sample collected from the western Pacific Ocean (Wang et al, 2008) and shown to be phylogenetically related to members of the genus Nitratireductor. At the time of writing, four novel species from this pyrenedegrading consortium have been described: Roseovarius pacificus , Oceanicola pacificus (Yuan et al, 2009), Bowmanella pacifica (Lai et al, 2009) and Alcanivorax pacificus (Lai et al, 2011a).…”
mentioning
confidence: 99%
“…(Fernandez-Martínez et al, 2003); 3, A. hongdengensis A-11-3 T (Wu et al, 2009); 4, A. borkumensis SK2 T (Yakimov et al, 1998). Data for catalase, oxidase, API 20NE and API ZYM for the three reference type strains were obtained from our previous study (Lai et al, 2011). The data for strain 19-m-6 T were obtained under the same conditions as used during that study (Lai et al, 2011).…”
mentioning
confidence: 99%
“…Data for catalase, oxidase, API 20NE and API ZYM for the three reference type strains were obtained from our previous study (Lai et al, 2011). The data for strain 19-m-6 T were obtained under the same conditions as used during that study (Lai et al, 2011). +, Positive; W, weakly positive; À, negative.…”
mentioning
confidence: 99%
See 2 more Smart Citations